PENUMBUHAN JIWA KEWIRAUSAHAAN MELALUI PELATIHAN PEMBUATAN SABUN LIDAH BUAYA PADA SISWA MAN 23 JAKARTA - Rahayu, Kun Mardiwati; Puspitasari, Ririrs Lindiawati; Cholidhazia, Putri (LPPM Universitas Bina Bangsa, 2025)
Aloe vera is a plant that is easy to cultivate and has great potential to be processed into various economically valuable products, especially in the cosmetics sector, such as soap. However, in the partner environment, the use of aloe vera has not been maximized and there is a low entrepreneurial spirit among students. As a solution, this community service activity aims to provide education about entrepreneurship as well as training in processing aloe vera into soap. This activity was carried out in stages, starting with providing insight into bioentrepreneurship, followed by practical training in making aloe vera soap. To evaluate this activity, questionnaires were given to students before and after training. The results of the activity showed that there was an increase in knowledge regarding entrepreneurship and soap making skills. This activity had a positive impact on participants in creating and running an aloe vera soap business